First record of scab disease of almond caused by Cladosporium carpophillum in India - MOHAMMED HUSSAIN, SABA BANDAY, MUSHTAQ A. BHAT; NISAR A. QAZI, NASSREEN F. KACHO*, KHURSHEED AHMED (Indian Phytopathology, 2017)
In India Almond (Prunus amygdulus Batsch.) is commercially grown in Jammu and Kashmir state. During 2012 -2014, circular to oval lesions with brown centers and slightly raised purple margins were observed on twigs of almond, while on leaves lesions appeared as many small, indistinct, somewhat circular, greenish yellow blotches under surface. On fruit, spots were dark grey to black sooty appearance that coalesced into large dark blotches. Average disease intensity of 24.30 per cent and 26.50 per cent was recorded on leaves and twigs respectively. The culture obtained from the diseased sample was identified as Cladosporium carpophillum Thum. on the basis of the colony and morphological characters. To our knowledge, this is the first report of scab of Almond fruit caused by C. carpophillum in India. This disease can seriously affect Almond quality and yield, so effective measures should be implemented to control it.